Orthodontic treatment with one lower incisor extraction. A case report - Vélez Taboada, Luis Carlos (2017)
A 22 year old woman with mesofacial biotype, skeletal class I and good lips profile, presented an Angle malocclusion class I with good intercuspidation of molars and premolars, moderate crowding in both arches, discrepancy of anterior Bolton for inferior excess, and decreased overjet and overbite. She was treated with a orthodontics treatment with extraction of a lower incisor, an atypical extractions in orthodontics. The success of this type of treatment needs a deep and meticulous diagnostic record, because this election of treatment will depend on a series of minimum requirements.